STRATEGI PENGEMBANGAN USAHA ROTI PADA INDUSTRI RUMAH TANGGA AISYAH BAKERY DI KOTA PALU - Irmawati, Irmawati; Lamusa, Arifuddin; Laihi, Moh. Alfit A. (Fakultas Pertanian, Universitas Tadulako, 2023)
Aisyah home industry is a business engaged in bread production, located at Jalan Simpati Number 8, South Palu District, Palu City. The main goal of this research was to identify the appropriate strategy for the development of Aisyah Bakery's home industry. It was carried out between August and September 2020. The analysis method used in this study was the SWOT analysis. Based on the SWOT matrix of IFAS and EFAS, the strategic position of Aisyah Bakery home industry falls within quadrant I, which represents the Strengths-Opportunities strategy. Consequently, several effective strategies have been identified for the bakery business development: (a) Enhancing production capacity by leveraging readily available tools and raw materials to meet market demand, with support from the government; (b) Utilizing self-generated capital to explore new market segments.